2002
DOI: 10.1128/cdli.9.2.344-347.2002
|View full text |Cite
|
Sign up to set email alerts
|

Immunocytochemical Method for Early Laboratory Diagnosis of Tuberculous Meningitis

Abstract: A simple immunocytochemical method was standardized for the direct demonstration of mycobacterial antigen in cerebrospinal fluid (CSF) specimens of patients with tuberculous meningitis (TBM). CSF-cytospin smears were prepared from 22 patients with a clinical diagnosis of TBM and also from an equal number of patients with nontuberculous neurological diseases (disease control). Immunocytological demonstration of mycobacterial antigens in the cytoplasm of monocytoid cells was attempted, by using rabbit immunoglob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
14
1

Year Published

2006
2006
2011
2011

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 11 publications
1
14
1
Order By: Relevance
“…In addition to measuring M. tuberculosisspecific antibodies or antibody-secreting cells, assays to measure M. tuberculosis-specific antigens directly in the CSF have also been evaluated (32,82,86,92,103,125,202,203,205,236) (Table 3). A theoretical advantage of antigen detection over antibody detection would be that they would be released only as a result of the host's immune response or the result of treatment.…”
Section: Molecular and Biochemical Analysismentioning
confidence: 99%
“…In addition to measuring M. tuberculosisspecific antibodies or antibody-secreting cells, assays to measure M. tuberculosis-specific antigens directly in the CSF have also been evaluated (32,82,86,92,103,125,202,203,205,236) (Table 3). A theoretical advantage of antigen detection over antibody detection would be that they would be released only as a result of the host's immune response or the result of treatment.…”
Section: Molecular and Biochemical Analysismentioning
confidence: 99%
“…In another study by Brienz et al, two PCR protocols showed low sensitivities (36% and 53% for the TB AMPLICOR assay and the MPB64 nested PCR, respectively) compared with those of classic microbiological methods (73% and 54% for Ziehl-Neelsen staining and culture, respectively) for the diagnosis of TBM in 91 patients in southeastern Brazil (3). An immunocytological method with CSF-cytospin smears was used by Sumi et al to detect Mycobacterium antigens in the cytoplasm of CSF monocytes and showed a sensitivity of 72% (20). The overall sensitivities of dot ELISA (for the detection of Mycobacterium antigen in CSF) and PCR were 75% and 40%, respectively (21).…”
mentioning
confidence: 99%
“…During the second stage, bacilli grow logarithmically within newly recruited macrophages (7). Thus, the cytoplasm of the macrophages in active TBM patients contains TBAg (23). Theoretically the positive immunostaining of cytoplasm of CSF macrophages means that viable tubercle bacilli are present.…”
mentioning
confidence: 99%
“…Theoretically the positive immunostaining of cytoplasm of CSF macrophages means that viable tubercle bacilli are present. Correspondingly, Sumi et al (23) reported that the method had promising sensitivity and specificity (72.5% and 100%, respectively). Nevertheless, the sample size in their study was relatively small (22 cases).…”
mentioning
confidence: 99%
See 1 more Smart Citation